Variable Responses to CFTR Correctors in vitro: Estimating the Design Effect in Precision Medicine - Matthes, Elizabeth; Goepp, Julie; Martini, Carolina; Shan, Jiajie; Liao, Jie; Thomas, David Y.; Hanrahan, John W. (Frontiers in Pharmacology, 2018)
Interest in precision medicine has grown in recent years due to the variable clinical benefit provided by some medications, their cost, and by new opportunities to tailor therapies to individual patients. In cystic fibrosis (CF) it may soon be possible to test several corrector drugs that improve the folding and functional expression of mutant CFTR prospectively using cells from a patient to find the one that is best for that individual. Patient-to-patient variation in cell culture responses to correctors and the reproducibility of those responses has not been studied quantitatively. We measured the functional correction provided by lumacaftor (VX-809) using bronchial epithelial cells from 20 patients homozygous for the F508del-CFTR mutation. Significant differences were observed between individuals, supporting the utility of prospective testing. However, when correction of F508del-CFTR was measured repeatedly using cell aliquots from the same individuals, a design effect was observed that would impact statistical tests of significance. The results suggest that the sample size obtained from power calculations should be increased to compensate for the group sampling effect when CFTR corrector drugs are compared in vitro for precision medicine.